Designed 1-Hydroxynaphthalene-2-Carboxanilide Derivatives were evaluated for their Anticancer drug candidate properties by performing a Silico Pharmacokinetic and Silico Toxicological Analysis - Ms. Kanij Ansari; Dr Sapna Jain Dabade; Mrs. Madhu Singh (The Bioscan, 2026)
Cancer continues to be a significant worldwide threat to health and there is a desperate requirement for more effective and safer anticancer agents. A total of seventy-five 1-hydroxynaphthalene-2-carboxanilide derivatives were tested systematically evaluated using computer-aided drug design methods in the present study with reference to Anticancer 1-hydroxynaphthalene-2-carboxanilides with a p53-independent mechanism of action were designed and synthesized. First, all seventy-five compounds were pre-screened for physicochemical and pharmacokinetic properties on [SwissADME](https://www.swissadme.ch) and thirty compounds were chosen for in-depth toxicity and pharmacokinetic analysis on [ADMETlab 3.0] (https://admetlab3.scbdd.com) with favourable ADME profiles. The study explored various aspects of the compounds, such as their physiochemical properties, LogP, aqueous solubility, drug kinetic parameters, drug-likeness, medicinal chemistry accessibility, and toxicity profiles, to thoroughly evaluate their therapeutic potential. The majority of the compounds showed good oral absorption, moderate water solubility and good lipophilicity (LogP of < 5.). Drug-likeness evaluation showed that the compounds tested had minimal rule violations with a consistent bioavailability score of 0.55. The BOILED-Egg model showed good gastrointestinal absorption and permeability characteristics, and the bioavailability radar showed that a few derivatives were located in optimal physicochemical area for an oral drug. The toxicity predictions indicated moderate toxicity profile with some compounds being low in hepatotoxicity and cardiotoxicity risk. In addition, the compounds selected were expected to not be substrates of P-glycoprotein, resulting in good membrane transport properties. Based on the integrated ADME and ADMET analysis, the five compounds (3, 14, 15, 16 and 26) were selected as the most suitable lead candidates for further drug development and evaluation as anticancer agents with balanced pharmacokinetic and safety profile. The results of this study indicate that in the future, 2-hydroxynaphthalene-3-carboxanilide derivatives can be used as scaffolds for designing new cancer drugs. Such derivatives can be capable of possessing better drug like properties.